PERAN GURU BIMBINGAN KONSELING DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK SMK NEGERI 1 KOLAKA - Faisal, Andi (IAI Al-Mawaddah Warrahmah Kolaka, 2021)
The role of a counseling guidance teacher at school is a teacher or educator who is responsible for providing assistance to students in avoiding or overcoming difficulties in their lives so that individuals can achieve prosperity. Therefore, the efforts of the counseling guidance teacher in overcoming the learning difficulties of students in the teaching and learning process in schools are urgent to be implemented. Because if students have learning difficulties, it will hinder their learning development. And this will affect the output of school education that is of low quality and quality. Based on this, this study aims to explain the role of counseling guidance teachers in overcoming the learning difficulties of students at SMK Negeri 1 Kolaka. The research used is a qualitative approach with a descriptive type. Sources of data include counseling teachers, principals, and students of SMK Negeri 1 Kolaka as the main data source and several other data sources. The data collection technique used is by conducting observations, interviews, and documentation. The results of this study indicate that the role of the counseling guidance teacher in overcoming the learning difficulties of the students of SMK Negeri 1 Kolaka, namely: planning a counseling guidance program, then identifying the problems faced by students. After finding the problems faced by students, then the students are given direction, motivation and understanding of the learning difficulties faced by students.